93: Quality Appraisal of Canadian Guidelines on the Perinatal Care of Potential Extremely Premature Infants: How do they Rate?. Issue 6 (1st June 2014) - Moore, G; Lemyre, B; Daboval, T; Dunn, S
Abstract: BACKGROUND: Many clinicians refer to published or local guidelines when counseling expectant parents about perinatal care decisions. The number of guidelines created and currently in use in Canada and the quality of those guidelines is unknown. OBJECTIVES: To assess the quality of guidelines created and used in Canada regarding the perinatal care of 22 to 25 week GA infants. DESIGN/METHODS: We contacted the 32 Canadian Neonatal Network centres to determine: 1) if they had created their own guideline; and, 2) what Canadian guideline(s) they used. Any guideline(s) used were retrieved for assessment with the validated Appraisal of Guidelines for Research & Evaluation (AGREE II) Instrument. This six-domain, 23-item instrument assesses guideline quality (eg, scope, stakeholder involvement, rigour and transparency of development, clarity of presentation, applicability, and editorial independence). Three reviewers independently assessed each guideline. Items with a score difference of >3 were reviewed to reach consensus on a revised score. RESULTS: Twenty-nine of the 32 centres responded (91%). Twenty-seven of the 29 centres used the national Canadian Pediatric Society (CPS) statement as a guideline. One centre used their regional guideline. An outborn centre reported the CPS statement did not apply to them. Two centres used local guidelines in addition to the CPS statement; only one provided their guideline. Therefore, one national, one regional and one local guideline were obtained and assessed with the AGREE-II instrument. Major deficits were found within all AGREE II domains for the three guidelines. The domains with the lowest scores were generally 'rigour of development' and 'applicability'. The overall quality score was 44%, 39%, and 33% for the national, regional and local guidelines, respectively. No guideline was deemed suitable for clinical use given the identified flaws. The national guideline was considered useable with many modifications. CONCLUSIONS: Several guidelines on the perinatal care of 22 to 25 week GA infants exist in Canada. Many deficits were identified in the quality of their development. The benefits of guidelines are dependent on their quality; therefore, the use of a poorly developed guideline may be detrimental to decision-making processes and patient care. Canada urgently needs a guideline with recommendations established through a rigorous and transparent development process.